Efficacy of pump-controlled selective antegrade cerebral perfusion in total arch replacement: A propensity-matched analysis - Liu, Yu; Jiang, Hui; Wang, Bin; Yang, Zhonglu; Xia, Lin; Wang, Huishan (Frontiers in Surgery, 2022)
Background Pump-controlled selective antegrade cerebral perfusion (PC-SACP) in total arch replacement (TAR) can regulate cerebral flow accurately, which might be beneficial for cerebral protection. However, the safety of PC-SACP for TAR combined with frozen elephant trunk implantation (FET) in patients with acute Type A dissections (ATAAD) is ambiguous. Methods A total of 192 patients with ATAAD underwent TAR at our institution from October 2019 to July 2021. The patients were divided into two groups based on PC-SACP used: PC group (SACP carried out by using a separate pump, n = 35) and Control group (SACP carried out as a traditional method, n = 157). Patients under PC-SACP were propensity-score matched to patients without PC-SACP, resulting in 35 pairs of patients. Results Preoperative characteristics, including age, gender, weight, and preoperative creatinine level, were similar between the two groups. Cardiopulmonary bypass time, cross-clamp time, circulatory arrest time, and minimum nasopharyngeal temperature did not differ between the two groups. However, SACP time (54 versus 40, P = 0.001) in the PC group was significantly longer than that in the Control group. The incidence of temporary neurologic dysfunction (5.7% versus 8.6, P = 0.643) showed a no significantly lower trend in the PC group compared with the Control group. Other clinical outcomes showed no significant intergroup differences. Conclusions PC-SACP in TAR is safe and feasible and might be beneficial for avoiding brain injury caused by “luxury” perfusion.